It s all just a game? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
A simulation game is another variation of a role play. They are often played as a board game, and through learning the game s rules, they are a fine way to learn or revisit fairly complex disciplines, such as management or credit